2013
DOI: 10.1155/2013/639502
|View full text |Cite
|
Sign up to set email alerts
|

Osteoconductivity and Biodegradability of Collagen Scaffold Coated with Nano‐β‐TCP and Fibroblast Growth Factor 2

Abstract: Nanoparticle bioceramics have become anticipated for biomedical applications. Highly bioactive and biodegradable scaffolds would be developed using nanoparticles of -tricalcium phosphate ( -TCP). We prepared collagen scaffolds coated by nano--TCP and fibroblast growth factor 2 (FGF2) and evaluated the effects on new bone augmentation and biodegradation. The collagen sponge was coated with the nano-TCP dispersion and freeze-dried. Scaffold was characterized by SEM, TEM, XRD, compressive testing and cell seeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 51 publications
0
41
0
Order By: Relevance
“…Ordinarily, the mechanical properties of the regenerative scaffold play a facilitative role in maintaining the space for ingrowth of cells and blood vessels from the surrounding tissue. 5 In the present examination, GO and RGO coatings significantly increased the compressive strength of the collagen scaffold, likely due to the GO nanosheet assembling on the strut surface of the collagen scaffold and adding to its elasticity. Furthermore, the compressive strength of the RGO-coated collagen scaffold was approximately two-fold greater than that of the GO scaffold.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Ordinarily, the mechanical properties of the regenerative scaffold play a facilitative role in maintaining the space for ingrowth of cells and blood vessels from the surrounding tissue. 5 In the present examination, GO and RGO coatings significantly increased the compressive strength of the collagen scaffold, likely due to the GO nanosheet assembling on the strut surface of the collagen scaffold and adding to its elasticity. Furthermore, the compressive strength of the RGO-coated collagen scaffold was approximately two-fold greater than that of the GO scaffold.…”
Section: Discussionmentioning
confidence: 47%
“…3 The surface morphology of the scaffold often has a profound effect on the attachment of surrounding cells and tissues after implantation. 4 Many investigators have reported that surface modification of scaffolds with nano-sized materials stimulates bioactivity, including cell proliferation, tissue compatibility, and biodegradability, 4,5 indicating that effective modification of the scaffold surface plays an important role in facilitating tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
“…β-TCP powder (Beta TCP; Tomita Pharmaceutical, Naruto, Japan) was pulverized into nano-sized particles using a pulverizer (Nanomizer, Yokohama, Japan). The peak profile of β-TCP powder via X-ray diffraction investigations was overlapped with the data of the previous report 27,32) . The β-TCP nanoparticles, along with the surfactant sodium cholate (0.2 wt%), were then dispersed in 1-methyl-2-pyrrolidone (Wako Pure Chemical Industries, Osaka, Japan).…”
Section: Fabrication and Characterization Of β-Tcp Nanoparticlemodifimentioning
confidence: 71%
“…Dispersion of β-TCP nanoparticles was carried out as described previously 27) . β-TCP powder (Beta TCP; Tomita Pharmaceutical, Naruto, Japan) was pulverized into nano-sized particles using a pulverizer (Nanomizer, Yokohama, Japan).…”
Section: Fabrication and Characterization Of β-Tcp Nanoparticlemodifimentioning
confidence: 99%
See 1 more Smart Citation